2001
DOI: 10.1161/01.cir.104.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Human Coxsackie-Adenovirus Receptor Is Colocalized With Integrins α v β 3 and α v β 5 on the Cardiomyocyte Sarcolemma and Upregulated in Dilated Cardiomyopathy

Abstract: Low hCAR abundance may render normal human myocardium resistant to CAR-dependent viruses, whereas re-expression of hCAR, such as that observed in DCM, may be a key determinant of cardiac susceptibility to viral infections. Asymmetric expression of hCAR in the vessel wall may be an important determinant of adenovirus tropism in humans. hCAR subcellular localization in human myocardium and hCAR targeting to cell-cell contacts in cardiomyocyte cultures suggest that hCAR may play a role in cell-cell contact format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(98 citation statements)
references
References 29 publications
5
93
0
Order By: Relevance
“…These are few and yet describe partially conflicting results [9,12,14]. With immunohistochemistry on tissue sections, high CAR expression has been demonstrated in the epithelium of normal human prostate [7], normal human bladder [15] and in head and neck squamous cell carcinoma [16], while very low CAR expression has been demonstrated in the normal human heart [17].…”
Section: Discussionmentioning
confidence: 99%
“…These are few and yet describe partially conflicting results [9,12,14]. With immunohistochemistry on tissue sections, high CAR expression has been demonstrated in the epithelium of normal human prostate [7], normal human bladder [15] and in head and neck squamous cell carcinoma [16], while very low CAR expression has been demonstrated in the normal human heart [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors have shown that cytokines upregulate coxsackie-adenovirus receptor (CAR) on human myocardium and that the level of CAR upregulation is a major determinant of susceptibility to cardiac infection by adenoviruses and coxsackie viruses. 34 Although the exact mechanism through which TNFa contributes to decreased contractile performance in myocarditis is not well known, a number of studies have emphasized the negative impact mediated by nitric oxide (NO). Finkel et al 35 showed that the depression of isolated papillary muscle contractile function caused by TNFa or IL6 was blocked when an L-arginine analogue was added as a specific inhibitor of NO synthase (NOS).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Following attachment, viral particles are internalized via integrin (a v b 3/5 )-mediated endocytosis following the interaction of the integrins with the viral penton base protein. [24][25][26][27] Two cancer cell lines (HT29 and DLD1) and two normal cells (human umbilical vein endothelial cells (HUVECs) and human mammary epithelial cells (HMEC)) were cultured under normoxia or hypoxia for 18 h, labeled with antibodies, fixed in paraformaldehyde, and then subjected to flow cytometry analysis for cell surface expression of these virus receptors. For all the cells tested, neither the expression of CAR nor integrin was altered by hypoxia ( Figure 2).…”
Section: Cell Surface Expression Of the Ad Attachment And Internalizamentioning
confidence: 99%